More answers

Lvl 1

Q

Q: 3x - 7 equals 5x plus 13?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3x+7=5x-13 ----> 3x-5x=-13-7 ----> -2x=-6 -----> x=3

If: 3x-7 = 5x+13 Then: x = -10

3x + 7 = 5x + 13 3x - 5x = 13 - 7 -2x = 6 -x = 3 x = -3

3x - 7 = 5x + 133x - 5x = 13 + 7-2x = 20x = -10x=-3

X=10.

Related questions

3x+7=5x-13 ----> 3x-5x=-13-7 ----> -2x=-6 -----> x=3

If: 3x-7 = 5x+13 Then: x = -10

3x + 7 = 5x + 13 3x - 5x = 13 - 7 -2x = 6 -x = 3 x = -3

3x - 7 = 5x + 133x - 5x = 13 + 7-2x = 20x = -10x=-3

x=-3

X=10.

5x+49 = 8x+13 49-13 = 8x-5x 36 = 3x x = 12

x = -13

(3, -4)

0. 7 - 3x = 5x + 13 1. 7 - 8x = 13 2. -8x = 5 3. x = -5/8.

3x + 9 = 5x - 43x +13 = 5x13 = 2x13/2 = xso x = 6.5

2x+3x = 5x